SWIMMING WITH SHARKS : The Daring Discoveries of Eugenie Clark - Lang, Heather, 1966-; Solano, Jordi (New York : AV2 by Weigl, 2019)
"The true story about the girl who grew up to be the 'Shark Lady' and became one of the most inspiring scientists in the world"--Back cover.
A biography of the scientist known as the "Shark Lady," reveals how she turned a childhood passion into her life's work, devoting herself to studying sharks and educating the public on the graceful, clever sea creatures.
AV2 Fiction Readalong by Weigl brings you timeless tales of mystery, suspense, adventure, and the lessons learned while growing up. These celebrated childrens stories are sure to entertain and educate while captivating even the most reluctant readers. Log on to www.av2books.com, and enter the unique book code found on page 2 of this book to unlock an extra dimension to these beloved tales. Real actors will bring the story to life as you read along in your own book.
First published in 2016 by Albert Whitman & Company.
Keywords: Clark, Eugenie -- Juvenile literature; Ichthyologists -- United States -- Biography -- Juvenile literature; Sharks -- Research -- Juvenile literature